2023
DOI: 10.3390/cancers15030992
|View full text |Cite
|
Sign up to set email alerts
|

Three Months’ PSA and Toxicity from a Prospective Trial Investigating STereotactic sAlvage Radiotherapy for Macroscopic Prostate Bed Recurrence after Prostatectomy—STARR (NCT05455736)

Abstract: Biochemical recurrences after radical prostatectomy (RP) can be managed with curative purpose through salvage radiation therapy (SRT). RT dose escalation, such as stereotactic RT (SSRT), may improve relapse-free survival in this setting. STARR trial (NCT05455736) is a prospective multicenter study including patients affected by macroscopic recurrence within the prostate bed after RP treated with SSRT. Recurrence was detected with a Choline or PSMA CT-PET. In the current analysis, the early biochemical response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Francolini et al conducted the STARR trial and reported early toxicity and biochemical outcomes after stereotactic salvage radiotherapy for macroscopic recurrence within the prostate bed after radical prostatectomy. They demonstrated an optimal tolerability profile and promising oncologic outcomes [ 9 ]. Yamazaki et al contributed to this Special Issue by providing two brachytherapy studies.…”
mentioning
confidence: 99%
“…Francolini et al conducted the STARR trial and reported early toxicity and biochemical outcomes after stereotactic salvage radiotherapy for macroscopic recurrence within the prostate bed after radical prostatectomy. They demonstrated an optimal tolerability profile and promising oncologic outcomes [ 9 ]. Yamazaki et al contributed to this Special Issue by providing two brachytherapy studies.…”
mentioning
confidence: 99%